A rare mode of entry for needles observed in the abdomen of children: Penetration - Bakal, Unal; Tartar, Tugay; Kazez, Ahmet (My University, 2012)
Report of incidentally detected sewing needles on plain abdominal radiographs in two patients without any prior history of ingestion or of being pierced: one in the liver and the other in the peritoneum encased by omentum. These case reports point out a rare mode of entry of needles into the abdominal cavity by penetration from outside.
Keywords: Abdomen; children; penetration; sewing needle